EFFECT OF CERIUM ON HYDRODESULFURIZATION CATALYST PERFORMANCE - Triyono Triyono; Wega Trisunaryanti (Indonesian Journal of Chemistry, 2008)
Effect of cerium on hydrodesulfurization catalysts performance have been investigated. The catalysts were Pt or Pt-Ce supported on zeolite. The Pt/Zeolite catalyst was prepared by wet impregnation method, while that of Pt-Ce/Zeolite catalyst was prepared using coimpregnation method both were followed by drying, calcination, oxidation and reduction. The catalysts activity test was performed in a micro reactor and products composition was determined using gas chromatography. The results showed that cerium enhanced catalyst performance especially catalyst lifetime. Therefore, the catalysts have higher tendency to remain active for longer period. Due to its function, cerium might be used as a promoter of hydrodesulfurization catalysts.